Evolutionary trends in the interpretation of the European Court of Human Rights under the European Convention on Human Rights - Карвацька, Світлана Богданівна; Blikhar, Mariia; Huralenko, Nataliia (CUESTIONES POLÍTICAS, 2021)
The purpose of this Article is to analyse evolutionary trends in the interpretation of the European Convention on Human Rights (ECHR) by the European Court of Human Rights (ECtHR). To achieve this goal, a wide range of general philosophical methods were used. The Article submits that the ECHR has shown a growing commitment to the evolutionary method of interpretation, using the doctrine of a «living instrument», the ECHR, which is particularly important for Member States with specific problems, although this method limits the scope in the discretion of the State. It is concluded that the interpretative methodology used by the ECHR involves the use of its methods, including increasingly developing methods of consensus, efficiency, judicial activism, comparison, innovative interpretation, autonomous method, and «balance» method. This demonstrates, inter alia, the unlimited potential to improve the ECHR’s interpretation of conventional standards. In the context of modern transformations in the direction of proactive international justice, judicial activism objectively departs from a formal application of legal norms and reflects the ECHR’s desire to protect the fundamental human rights of individuals and communicatethem.
Tendencias evolutivas en la interpretación del Tribunal europeo de Derechos Humanos en el marco del Convenio Europeo de Derechos Humanos
Keywords: evolutionary trends in legal interpretation; European Court of Human Rights; interpretation of rules of international law; consensus method; judicial activism